KESULITAN SISWA DALAM MEMAHAMI MATERI PECAHAN BERDASARKAN TEORI POLYA DI KELAS V SEKOLAH DASAR 93 PALEMBANG - Dwi Syahrani Dwi; Nila Kesumawati; Endie Riyoko (STKIP Subang, 2024)
This research aims to determine students' difficulties in understanding fractionmaterial based on Polya theory, find out what factors influence students inunderstanding fraction material based on Polya theory, and how to overcomestudents' difficulties in understanding fraction material based on Polya Theory inclass V of SD Negeri 93 Palembang. Type of qualitative descriptive research. Theresearch subjects were fifth grade students at SD Negeri 93 Palembang. The datacollection techniques used are observation, interviews, tests, documentation andinterviews (student learning outcomes). The results of this research show that (1) inthe indicator of understanding the problem there are 31 students who are able tounderstand the problem, in the indicator of making plans in 1b there are 23 studentsand for the indicator of making plans in 2b there are 20 students who are able tomake plans, in the indicator of implementing plan in 1c it is known that 21 studentswere able to solve the questions well and for the indicator of implementing the planin 2c there were 13 students, many students had difficulty in implementing the plan,in the indicator of implementing the plan in 1d there were 22 students and for theindicator of checking again in 2d there were as many as 13 students and for 1 e asmany as 24 students and for 2e as many as 23 students were able to reach thestage of re-examining the solutions achieved, (2) Factors of student difficulty inlearning fraction material include internal and external factors, (3) How to overcomedifficulties students in understanding fraction material, namely (a) Approachingstudents, (b) Repeating lessons that have not been understood, (c) Providingremedial measures for students who get low grades, (d) Using interesting models,methods and learning media and fun so that students understand more easily whenlearning takes place.